2020
DOI: 10.1186/s12939-020-01167-7
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in reproductive health care use in five West-African countries: A decomposition analysis of the wealth-based gaps

Abstract: Background: Family planning and maternal care services have become increasingly available in West Africa but the level of non-use remains high. This unfavorable outcome may be partly due to the unaffordability of reproductive health care services. Methods: Using the Demographic Health Survey data from Burkina Faso, Niger, Nigeria, Ghana, and Senegal, we perform a decomposition analysis to quantify the contribution of socio-demographic characteristics to disparities in exposure to mass media information on fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
4
19
0
3
Order By: Relevance
“…Our results corroborate many ndings on the existence of health inequalities between socioeconomic strata, with the richest being more likely to use health care than the poorest [31] [1], [6] [32] [11], [10]. In addition, women, people over 60 years of age and children under ve years of age are more likely to use care.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results corroborate many ndings on the existence of health inequalities between socioeconomic strata, with the richest being more likely to use health care than the poorest [31] [1], [6] [32] [11], [10]. In addition, women, people over 60 years of age and children under ve years of age are more likely to use care.…”
Section: Discussionsupporting
confidence: 89%
“…To ll this gap, a growing number of studies have used a method called the decomposition of Oaxaca and Blinder [7] [8] to tackle variables such as spatial variations of health care utilisation, wealth-based gaps, evolution of health care use over time, and ethnic disparities in access to social services [9] [10] [11]. There is a gap in the literature that deals with the disparities in health care utilisation based on the degree of protection against health hazards.…”
Section: Introductionmentioning
confidence: 99%
“…As in the literature on determinants of antenatal care use in developing countries , research in Egypt has confirmed the importance of both social and health needs as determinants of antenatal care [14,18,19,25,27]. On the social side, women's age or age at birth, their education, their husbands' education level, the women's work status, the household standard of living/wealth, and place of residence, assessed in terms of regional level or by rural/urban differentiation, were identified as significant determinants of antenatal care [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][31][32][33][34]. On the health dimension, most research highlighted the significant contribution of parity/birth order, previous birth experience, attributes of current pregnancy (in particular preceding birth interval), the survival status of the previous birth, and the experience of a terminated pregnancy [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Determinants and Inequality Of Antenatal Care In Egyptmentioning
confidence: 99%
“…Of the two rounds used in the current study the wealth index was only available in 2014. As a result, the wealth index for the data from the EDHS 1995 was calculated using the Principal component analysis on the same list of physical characteristics and consumer durable goods reported by Macro International for the production of the wealth index [30,31].…”
Section: Data Sources and Study Variablesmentioning
confidence: 99%
“…These efforts used different approaches in measuring inequality, including modeling the different factors that affect the use of maternal health services for the different social groups [23] and identifying the main determinants for each social category. Other research efforts have implemented a summary measure of inequality for different maternal health measures, in particular the concentration index and its decomposition to the contribution of their determinants including use of antenatal care [23][24][25][26]. Inequalities in antenatal care use have received signi cant attention from researchers in Egypt.…”
Section: Determinants and Inequality Of Antenatal Care In Egyptmentioning
confidence: 99%